2019
DOI: 10.1371/journal.pone.0223605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary intake and nutritional status on cerebral oxygenation in patients with chronic kidney disease not undergoing dialysis: A cross-sectional study

Abstract: BackgroundDietary management is highly important for the maintenance of renal function in patients with chronic kidney disease (CKD). Cerebral oxygen saturation (rSO2) was reportedly associated with the estimated glomerular filtration rate (eGFR) and cognitive function. However, data concerning the association between cerebral rSO2 and dietary intake of CKD patients is limited.MethodsThis was a single-center observational study. We recruited 67 CKD patients not undergoing dialysis. Cerebral rSO2 was monitored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Cerebral rSO 2 values in CKD patients without dialysis therapy (approximately 55–60%) and those undergoing HD (approximately 40–50%) were reportedly lower than those in healthy controls (approximately 70%) 15 18 , 35 . Furthermore, these values were reportedly associated with eGFR, serum albumin concentration, serum sodium concentration, hemoglobin level, energy intake, and energy intake/salt intake in CKD patients without dialysis therapy 17 , 18 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Cerebral rSO 2 values in CKD patients without dialysis therapy (approximately 55–60%) and those undergoing HD (approximately 40–50%) were reportedly lower than those in healthy controls (approximately 70%) 15 18 , 35 . Furthermore, these values were reportedly associated with eGFR, serum albumin concentration, serum sodium concentration, hemoglobin level, energy intake, and energy intake/salt intake in CKD patients without dialysis therapy 17 , 18 .…”
Section: Discussionmentioning
confidence: 89%
“…Cerebral rSO 2 values in CKD patients without dialysis therapy (approximately 55–60%) and those undergoing HD (approximately 40–50%) were reportedly lower than those in healthy controls (approximately 70%) 15 18 , 35 . Furthermore, these values were reportedly associated with eGFR, serum albumin concentration, serum sodium concentration, hemoglobin level, energy intake, and energy intake/salt intake in CKD patients without dialysis therapy 17 , 18 . In the evaluation of cognitive performance using the MMSE score in patients undergoing HD, cerebral rSO 2 values in patients with cognitive impairment (MMSE score ≤ 23) were reported to be significantly lower than those with normal cognition (MMSE score ≥ 24), and cerebral rSO 2 represented a positive and independent association with the MMSE score 36 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A bunch of clinical studies have shown that dietary sodium restriction has protective effect on the kidney of patients with CKD. [36][37][38] The mechanism of the effect may be associated with regulation of glomerular filtration and the reduction of local activation of renin-angiotensin-aldosterone system. Our study indicates that the decrease of urinary sodium excretion after restriction of dietary sodium might improve the binding ability of UMOD with cFH and inhibit complement activation.…”
Section: Discussionmentioning
confidence: 99%
“…We used a 3-day food diary to assess sodium intake, a method that may imply inherent errors of dietary assessment and can be the cause of under-and over-reporting. Nevertheless, there is large recent evidence that the 3-day diet diary is a simple, useful, and effective method to measure the intake of macro-and micro-nutrients in patients on chronic hemodialysis [43][44][45][46][47]. The strength is that we included patients of different towns of Italy and consequently the data can be considered representative of the Italian population of patients on chronic hemodialysis.…”
Section: Discussionmentioning
confidence: 99%